Research Progress on the Protective Effects of Active Components of Huangqi (Astragali Radix) on Pancreatic β-Cells - Yan, Liyi; Li, Zhenhua; Chen, Yuan (Chinese medicine and natural products, 2025)
The potential application of Huangqi (Astragali Radix) in the treatment of diabetes mellitus (DM) has garnered increasing attention. β-cell dysfunction is one of the core mechanisms in the pathogenesis of DM and effectively protecting and restoring pancreatic β-cell function remains a key challenge in DM prevention and treatment. Studies have shown that the active components of Huangqi (Astragali Radix) can alleviate glucolipotoxicity-induced β-cell damage by promoting glucose uptake mediated by glucose transporter 4 (GLUT-4), inhibiting the Wnt1/β-catenin signaling pathway to reduce lipid deposition in liver and pancreatic tissues and upregulating peroxisome proliferator-activated receptor α (PPARα) gene expression. Additionally, Huangqi (Astragali Radix) can reduce cell apoptosis by mitigating endoplasmic reticulum stress, suppress pyroptosis via the NF-κB/NLRP3/TXNIP signaling pathway, and inhibit ferroptosis and autophagy to decrease β-cell death. Furthermore, Huangqi (Astragali Radix) can promote β-cell proliferation by modulating dedifferentiation and transdifferentiation, improve the islet microenvironment by regulating immune function and reducing M1 macrophage polarization, and may delay β-cell senescence. This review summarizes the research progress of active ingredients in Huangqi (Astragali Radix) in protecting pancreatic β-cell, which provides new insights and a scientific basis for its future application in DM prevention and treatment.
Keywords: Huangqi; Astragali Radix; pancreatic β-cells; diabetes mellitus; glucose and lipid metabolism; cell death; senescence